2017
DOI: 10.7454/uiphm.v1i0.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethanol Extract Of Sarang Semut Plant (Hypnophytum Formicarum) to Granulation Tissue for Wound Healing After Teeth Extraction Experimental Research on Marmot (Cavia cobaya)

Abstract: Tooth extraction is a common thing, more often after extraction patients have any complication, to prevent it, physician provide some drugs from chemicals that often give adverse effects, so that required for a safe substitute medicine, which derived from herbs. One of the herbs are often used by people in the Mentawai Islands is a sarang semut's root species of Hypnophytum formicarum jack. This study aimed to determine the effect of sarang semut's extract orally for granulation tissue formation in wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, the extract was applied topically, whereas in previous studies, it was administered orally. 9,11 With regard to angiogenesis, this study indicates that the topically applied Hydnophytum formicarum plant extract can significantly reduce angiogenesis that occurs during the early, middle and late prolifera tion phases. This result is consistent with research by Ismardianita et al, who concluded that the oral adminis tration of the Hydnophytum formicarum plant extract at a dose of 6.2 mg was able to significantly reduce angio genesis in the proliferation phase.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Moreover, the extract was applied topically, whereas in previous studies, it was administered orally. 9,11 With regard to angiogenesis, this study indicates that the topically applied Hydnophytum formicarum plant extract can significantly reduce angiogenesis that occurs during the early, middle and late prolifera tion phases. This result is consistent with research by Ismardianita et al, who concluded that the oral adminis tration of the Hydnophytum formicarum plant extract at a dose of 6.2 mg was able to significantly reduce angio genesis in the proliferation phase.…”
Section: Discussionmentioning
confidence: 75%
“…This result is consistent with research by Ismardianita et al, who concluded that the oral adminis tration of the Hydnophytum formicarum plant extract at a dose of 6.2 mg was able to significantly reduce angio genesis in the proliferation phase. 9 By contrast, research conducted by Putri and Ismardianita found that the orally administered Hydnophytum formicarum plant extract at a dose of 4.65 mg was able to significantly increase angio genesis. 13 Wound healing with minimal to no scarring oc curs in the oral mucosa and the fetal skin in the uterus, pre senting less angiogenesis as compared to wound healing in the skin; however, the capillaries become mature more rapidly.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations